Ciclo biológico y comportamiento de tetrastichus howardi olliff en puparios de billaea (paratheresia) claripalpis wulp - Limo Cruz, Sisy Margarita (2017)
Tetrastichus howardi Olliff, parasitoid pupae of several lepidoptera has been registered in Diatraea saccharalis and is used as the insect control agent in the cultivation of sugar cane in Cuba. In Peru, this parasitoid, under laboratory conditions, behaves like a hyperparasite in pupae of Billaea claripalpis, parasitoid of larvae of D. saccharalis. The objective was to determine the biological cycle and some aspects of the behavior of T. howardii in puparia B. claripalpis in laboratory and field. The experiment was performed with two treatments and three replicates for each. The core breeding Tetrastichus from the host D. saccharalis was exposed to pupae of Billaea from their hosts D. sacchararlis and Galleria mellonella, and the biological cycle, hyperparasitic behavior, number of emerged individuals and percentage of emergence were determined. The duration of development stages of egg, larva and pupa, at 21 ° C, RH 56%; 23 ° C, 58% RH and 25 ° C, 60% RH, was 5, 8 and 17; 4, 6 and 14; And 1, 5 and 12 days respectively; Being the total cycle of 30, 24 and 18 days. The hyperparasitic behavior, during the five days of development, was 50; 22.8; 14.7; 4.8 and 0% respectively. The number of average individuals emerged by parasitized puparia from Diatraea and Galleria was 73,24 and 73,04 and parasitism in the laboratory was 75%; while in field it was null. That is why T. howardi under laboratory conditions acts as hyperparasite in puparia of Billaea claripalpis, being forced to parasite another host to maintain its survival.